Redo cardiac surgery for active prosthetic valve endocarditis associated with hereditary hemorrhagic telangiectasia: report of a case - Nakamura, Yuki (Surg Today, 2014)
Hereditary hemorrhagic telangiectasia (HHT) is caused by an autosomal dominant gene and characterized by multiple arteriovenous malformations in several organs, leading to bleeding or shunting. These patients often suffer severe infections and heart failure, which should be managed in the perioperative period, when open heart surgery is indicated. We report a case of successful aortic root replacement for active prosthetic valve endocarditis and ventricular septal perforation in a patient with HHT, who had severe heart failure.